Kepemimpinan Konteks Komunikasi Organisasi di Lingkungan Polri : (Antisipasi Paparan Radikalisme dan Terorisme di Sat Brimob Polda Sumatera Utara) - Muhammad Iqbal Pohan (Prisani Cendekia Institute, 2022)
Polri were the unique organization with leadership model different with other government institutions. Command system leadership is famous model for this one, because the impact of military organization in the past. The research talk about how the leadership model in communication organization studies in Polri come to anticipate radicalism and terrorism in their member, especially for Mobile Brigade (special police) as law enforcement. The theoretical studies this research was leaderships functions from Yammarino (1999). Qualitative model was the data processing for this research, and the researcher had interviewed (depth) any leader of Mobile Brigade region in Provincial Police North Sumatera. Finding this research shows that leadership Polri organization always base on the mature planning, local genius approach, motivation and police member mental endurance. Police leaderships more attention for emphatics to observe their members to get evaluate the terrorism and radicalism in their members.